2007
DOI: 10.1152/jn.00011.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Selectivity to Intracochlear Electrical Stimulation in the Inferior Colliculus is Degraded After Long-Term Deafness in Cats

Abstract: Vollmer M, Beitel RE, Snyder RL, Leake PA. Spatial selectivity to intracochlear electrical stimulation in the inferior colliculus is degraded after long-term deafness in cats. J Neurophysiol 98: 2588 -2603, 2007. First published September 12, 2007 doi:10.1152/jn.00011.2007. In an animal model of electrical hearing in prelingually deaf adults, this study examined the effects of deafness duration on response thresholds and spatial selectivity (i.e., cochleotopic organization, spatial tuning and dynamic range) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 94 publications
4
19
0
Order By: Relevance
“…Some of the experimental procedures have been described in detail in previous reports (e.g., Beitel et al 2000aBeitel et al , 2011Schreiner and Raggio 1996;Snyder et al 1995;Vollmer et al 2001Vollmer et al , 2007 and will be repeated here in an abbreviated form. All surgical and experimental procedures were approved by the Institutional Animal Care and Use Committee of the University of California, San Francisco and conformed to the guidelines of the National Institutes of Health for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the experimental procedures have been described in detail in previous reports (e.g., Beitel et al 2000aBeitel et al , 2011Schreiner and Raggio 1996;Snyder et al 1995;Vollmer et al 2001Vollmer et al , 2007 and will be repeated here in an abbreviated form. All surgical and experimental procedures were approved by the Institutional Animal Care and Use Committee of the University of California, San Francisco and conformed to the guidelines of the National Institutes of Health for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…Cochlear hair cell loss also leads to morphological and functional changes in central parts of the auditory system. These occur among others in the large axosomatic endings of the auditory nerve in the cochlear nucleus (Ryugo et al, 2010) and in its projection (Leake et al, 2006), as well as in the inferior colliculus (Vollmer et al, 2007) and auditory cortex (Ryugo et al, 1995;Kral and Tillein, 2006). These changes may in turn enhance the degeneration of SGCs since, besides afferent connections from hair cells, efferent connections from higher centers are thought to play a role in SGC survival (e.g., Hegarty et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies in animals demonstrated a strong correlation between the laminar organization of neurons and the tonotopic geometry of the IC. 18,19 Morest and Oliver showed that the IC consists of neural layers analogous to those observed across different species. 14 These layers correspond to different frequency laminae and justified a closer examination of the surgical challenges reaching the IC and positioning an auditory prosthesis.…”
Section: Discussionmentioning
confidence: 89%